Structural glance into a novel anti‐staphylococcal peptide. Issue 1 (January 2014) - Iannucci, N. B.; Curto, L. M.; Albericio, F.; Cascone, O.; Delfino, J. M.
ABSTRACT Novel antimicrobial peptides are valuable molecules for developing anti‐infective drugs to counteract the contemporary spread of microbial drug‐resistance. Here we focus on a novel peptide (RKWVWWRNR‐NH2) derived from the fragment 107–115 of the human lysozyme that displays a 20‐fold increase in anti‐staphylococcal activity. The conformational analysis of this peptide and its interaction with model lipidic phases—as assayed by circular dichroism and fluorescence spectroscopy—show a noteworthy spectral change, which might be related to its anti‐staphylococcal activity. The secondary structure of peptide [K108W111] 107–115 hLz was dramatically affected through a single substitution at position 111 (Ala by Trp). Therefore, this conformational change might improve the interaction of the novel peptide with the bacterial plasma membrane. These results highlight the role of peptide secondary structure and the distribution of polar/nonpolar residues for the effective interaction of this peptide with the bacterial plasma membrane, a key step for triggering its lethal effect. This knowledge may contribute to the rational design of a new generation of antimicrobial peptides with increased efficacy developed from natural sources by simple screening tools. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 49–57, 2014.